Penilaian Aspek Hukum Tata Kelola Hutan Tanaman Rakyat di Kabupaten Barru - Fahrum Ahmad; Yusran Yusran; Emban Ibnurusyd Mas'ud (Fakultas Kehutanan, Universitas Hasanuddin, 2017)
This study aims to identify the law products in community plantation forest (HTR) management in Barru and to evaluate the law products according to the principles of good governance. This study assessed all of law products related with community plantation forest that were used as guidelines for management implementation in Barru with the principles of good governance. The results showed that there were18 rules guiding the governance of HTR in Barru consisted of 12 rules made by the central government and 6 rules made by local government. The results of this assessment showed that the legal aspects in the governance of HTR in Barru categorised in the medium category (with a value of 1.81). The four aspects analyzed showed the portrait of the law in the governance of HTR (tenure 1,71; forest land use palnning 1,84; forest management 2,34; and forest revenues and economic incentives 1,31).